The Efficacy of the Modified Cycles Phonological Remediation to Enhance Speech for Hearing-Impaired Children - Ciao-Yi Ke; Kai-Mei Chen; Chu-Hsiu Teng (National Taipei University of Education, 2022)
The purpose of this study was to investigate the efficacy of the Modified Cycles Phonological Remediation (MCPRA) to enhance speech for children with severe speech sound disorders (SSD) and hearing impairment (HI). A multiple baseline design across subjects was used to examine intervention effects. Three preschoolers with severe SSD and HI at age ranging from 4 year 0 month to 6 year 4 month participated in the study. All three children received two cycles with 18 hours of phonological remediation sessions. The target generalization probe words were administered during baseline, intervention, and follow-up phases to assess generalization and maintenance of phonological skills. Data were analyzed by visual analysis, effect size and C-statistic. The results indicated that all participants' target generalization probe words exhibited significant improvement by the end of the intervention, maintain, and follow-up phase. Furthermore, three children's speech rating has improved from severe to mild or normal. Their speech intelligibility increased as well. This study provides evidence-based research on speech therapy for children with HI, and clinical procedure for MCPRA, including sounds analysis method, target selection, and the intervention steps. Finally, the result of this study could provide clinical and research application of the articulation/phonological intervention for Mandarin-speaking children with HI.